If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5.4(s + -3t) + 3.6(s + -4) = 0 (s * 5.4 + -3t * 5.4) + 3.6(s + -4) = 0 (5.4s + -16.2t) + 3.6(s + -4) = 0 Reorder the terms: 5.4s + -16.2t + 3.6(-4 + s) = 0 5.4s + -16.2t + (-4 * 3.6 + s * 3.6) = 0 5.4s + -16.2t + (-14.4 + 3.6s) = 0 Reorder the terms: -14.4 + 5.4s + 3.6s + -16.2t = 0 Combine like terms: 5.4s + 3.6s = 9s -14.4 + 9s + -16.2t = 0 Solving -14.4 + 9s + -16.2t = 0 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '14.4' to each side of the equation. -14.4 + 9s + 14.4 + -16.2t = 0 + 14.4 Reorder the terms: -14.4 + 14.4 + 9s + -16.2t = 0 + 14.4 Combine like terms: -14.4 + 14.4 = 0.0 0.0 + 9s + -16.2t = 0 + 14.4 9s + -16.2t = 0 + 14.4 Combine like terms: 0 + 14.4 = 14.4 9s + -16.2t = 14.4 Add '16.2t' to each side of the equation. 9s + -16.2t + 16.2t = 14.4 + 16.2t Combine like terms: -16.2t + 16.2t = 0.0 9s + 0.0 = 14.4 + 16.2t 9s = 14.4 + 16.2t Divide each side by '9'. s = 1.6 + 1.8t Simplifying s = 1.6 + 1.8t
| 3x+27=49x+21 | | 14a+14b+3c+5c-3b-3a= | | f(t)=15t+200 | | -x/8=-4 | | K-[-3]=28 | | -7(-11+2y)-2y=-13 | | 5(12-x)-11(4x-5)=9(-5x)-26 | | 3+8(st+3w)+3st= | | 16=3-7k-1 | | 15p+19q+p-3q-6p= | | 3x-2x+7=15 | | 12-4p=-4-6p | | 4cos^2x+4sin-1=0 | | 6.2(a+b)+2.6(a+b)+3a= | | 8t^2+3t+24=0 | | t/3-4=9 | | 8m=-12+5m | | 3x+2y+4(3x+y)= | | 2+(x+3)= | | 11*y=-22 | | 4x+3x+28=2 | | -9+5=-22 | | 6(x+2)+3(3x+7)=4(5+4x)-7 | | 7+3(uv-6)+u= | | r-8=9 | | C^2-14c+49=0 | | 50=d-0.5d | | 21-14x=29+12x | | y=7/3(-3)+5 | | 4(2x+y)+5x= | | 20-5(p+1)+3p=(2p-15) | | -x+(-2x)= |